Analysis of Milking Hygiene and Its Association to Staphylococcus Aureus Contamination in Fresh Cow Milk - Nurus Saffana Yulianto; Yunita Armiyanti; Dini Agustina; Bagus Hermansyah; Wiwien Sugih Utami (Universitas Airlangga, 2023)
Introduction: Staphylococcus aureus foodborne disease is caused by the consumption of food contaminated with Staphylococcus aureus enterotoxins. Milk is a type of food that contains many nutrients but is susceptible to contamination by Staphylococcus aureus. Jember is one of the districts in East Java that produces cow milk. Previous research showed that the level of milk consumption in the community in 2018 was 3.1 kg/capita/year and 42% consumed pasteurized milk, which has lower quality and may still be contaminated with bacteria. The purpose of this study was to determine the relationship between milking hygiene and Staphylococcus aureus contamination. Methods: A cross-sectional study was conducted involving 36 cow milkers with traditional milking, selected by total sampling. The independent variable was milking hygiene and the dependent variable was Staphylococcus aureus contamination. Milking hygiene practice data were collected through direct observation using a questionnaire. Staphylococcus aureus contamination data were tested using Total Plate Count (TPC) and identified using Gram staining and catalase tests. Results and Discussion: The TPC test results showed that 61.1% of cow's milk fulfilled the Indonesian National Standard for Staphylococcus aureus contamination. There was a relationship between milking hygiene and Staphylococcus aureus contamination. The most influential milking hygiene was cage, udder, and teat hygiene. Conclusion: Staphylococcus aureus contamination did not meet the standards. Therefore, improving the sanitation and hygiene of cages, as well as udder and teat hygiene by dairy farmers, is necessary.